UANG DAN KEKUASAAN POLITIK - Nurul Wahidah, Siti Isnaini (Universitas Hamzanwadi, 2017)
Vote buying is abnormal politic but is massive practice in Indonesian General Election. Curriculum vitae and professional popularity was substitute with money and goods. With observation, interview, and documentary technique this article assumed there are not something new in vote buying practices in Indonesian politics.Keywords : General Election, Vote buying